2010
DOI: 10.1186/1471-2458-10-579
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of high sensitivity C-reactive protein to percent body fat mass, body mass index, waist-to-hip ratio, and waist circumference in a Taiwanese population

Abstract: BackgroundHigh-sensitivity C-reactive protein (hs-CRP) is an easily measured inflammatory biomarker. This study compared the association of percent body fat mass (%FM), body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) with hs-CRP in a Taiwanese population.MethodsA total of 1669 subjects aged 40-88 years were recruited in 2004 in a metropolitan city in Taiwan. The relationships between obesity indicators and a high level of hs-CRP were examined using multivariate logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 37 publications
3
33
1
4
Order By: Relevance
“…As such, in the Framingham study , visceral adipose tissue (assessed by multidetector computed tomography) was associated with CRP after controlling for BMI and waist circumference, suggesting that BMI or waist do not completely account for visceral adiposity. Consistently, percentage body fat mass was reported to be a better predictor of high serum levels of CRP than any of the anthropometric measures in a Taiwanese population study . However, it is useful to understand the association between serum CRP and anthropometric measures as they are more convenient to measure.…”
Section: Discussionmentioning
confidence: 91%
“…As such, in the Framingham study , visceral adipose tissue (assessed by multidetector computed tomography) was associated with CRP after controlling for BMI and waist circumference, suggesting that BMI or waist do not completely account for visceral adiposity. Consistently, percentage body fat mass was reported to be a better predictor of high serum levels of CRP than any of the anthropometric measures in a Taiwanese population study . However, it is useful to understand the association between serum CRP and anthropometric measures as they are more convenient to measure.…”
Section: Discussionmentioning
confidence: 91%
“…In another population-based study, the percentage of fat mass explained the highest percentage of the variability of CRP in women [30]. Lin et al reported that the percentage of body fat mass was strongly associated with elevated hs-CRP levels in both genders [32].…”
Section: Discussionmentioning
confidence: 92%
“…A few studies have used measures of body fat to investigate the association between hs-CRP and obesity [29][30][31][32]. In monozygotic twins, CRP concentration was strongly related to both total and central abdominal obesity, independent of genetic influences [29].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for these results is that adipocytes are the major source of basal IL-6 and TNF-a secretion, which are the primary stimuli for hepatic CRP production [47]. Therefore, the sensitivity of CRP as a biomarker of inflammation is lower in overweight/obese women, as this is a cytokine, which is usually in high concentration when there is a substantial fat store [48][49][50]. Only these two studies stratified the analysis by BMI, which proved to be a better analytical strategy than the simple inclusion of BMI as a covariate in logistic or linear models.…”
Section: Discussionmentioning
confidence: 99%